Significance of polycyclic aromatic hydrocarbons (PAHs) in Permian/Triassic boundary sections - Nabbefeld, Birgit; Grice, Kliti; Summons, R; Hays, L; Cao, C (Elsevier, 2010)
In this study the abundances of several polycyclic aromatic hydrocarbons (PAHs Table 1, I-XXI) havebeen measured throughout three Permian/Triassic (P/Tr) sections from Meishan (South China), Kap Stosch area (East Greenland) and Peace River Basin (Western Canada). Dibenzothiophene (I) and dibenzofuran (II) were found to decrease in abundance just before or shortly after the P/Tr transition in all three sections while perylene (III) was observed to increase in abundance at the onset of the main extinction horizon (bed 25) in Meishan. Perylene has been attributed to a wood degrading fungal source and, therefore, it seems possible these phenomena are related to the demise of land plants. Further, distinct patterns of various combustion-derived PAHs occurring in each section imply that forest fire events occurred within the Late Permian and Early Triassic. In the Meishan section high amounts of combustion- derived PAHs [pyrene (IV), fluoranthene (V), benzo[a]anthracene (VI), benzofluoranthenes (sum, i.e. VII), benzo[a]pyrene (VIII), benzo[e]pyrene (IX) and coronene (X)] occur within bed 25, also containing ash attributed to the fallout from massive volcanic eruptions in Siberia and/or China.